Impacts of reducing food loss and waste on food prices and farm incomes - Vos, Rob (National Academies Press, 2019)
Suzanne Thornsbury, chief of the Crops Branch in the Market and Trade Economics Division, U.S. Department of Agriculture Economic Research Service, served as moderator for a panel on the impacts of food loss and waste on food prices and farm incomes.